A steady-state RF inductively coupled plasma source for plasma processing - Xu, Shuyan (2008)
This project aims at developing the low-frequency, uniform and high density plasma source for materials processing. The uniform, large (32 cm in diameter), high-density plasma source capable of rapid processign of large substrates has been developed and investigated both theoretically and experimentally.